Groves, sacred, Greece and Rome - Bonnechere, Pierre (The Encyclopedia of Ancient History, 2013)
The “sacred grove” (Greek alsos, plural alse; Latin lucus or nemus) is a difficult concept to define. Theoretically, it differs from wild wood, flower and vegetable garden, vineyard, and orchard. Yet the overlap among these concepts is such that precise distinction proves impossible. Since the definitions by late lexicographers rely more on deductive reasoning than on any real knowledge, their statements are inconclusive and sometimes in contradiction to concrete cases. Archaeological evidence has long been disappointing: landscaping has only recently attracted the attention of researchers, but many sanctuaries were excavated long ago. However, recent excavations seem promising.